Significance of Abu Dujana and Zarkasih's verdict - Nurfarahislinda Mohamed Ismail (2009)
The first ever Indonesian court ruling of convicts as terrorists and the branding of the Jemaah Islamiyah (JI) organisation as a "terrorist" one is examined in great detail in this paper. Beginning with the historical development of other counter-terror trials that took place in the Archipelago, it attempts to compare the cases of Abu Dujana and Zarkasih to their precedents and highlights some of its downplayed, but astonishing significances. It also takes a look at the reasons behind the reluctance of the government in banning the JI and suggests possible implications resulting from the verdict.